Planning, composition, and revision: Writing skills in university students with and without dyslexia - Carnota, Andrés; Suárez-Coalla, Paz (Revista de Investigación en Logopedia, 2025)
Dyslexia is a specific difficulty affecting writing skills, even in highly educated adults. This study analyzes planning, written composition, and revision skills in the production of an argumentative text by 40 Spanish university students with and without dyslexia. Participants completed a task divided into three phases: planning, composition, and revision. Regarding text quality, significant differences were observed in the cohesion scale, while the remaining scales did not yield conclusive results. Additionally, the types of errors committed by both groups and their ability to effectively correct them were analyzed. The dyslexic group made more spelling, accentuation, and punctuation errors, which persisted after the revision phase. However, both groups carried out a similar number of lexical-semantic revisions aimed at improving their texts. These findings highlight specific difficulties in planning and revision among adults with dyslexia and underscore the need for interventions targeting these skills to bring their performance closer to that of their peers without dyslexia.